The Bildungsroman of diasporic muslim women : a study of Mohja Kahf's The Girl in the Tangerine Scarf (2006) and UMM Zakiyyah's Realities of Submission (2008) - Aisyah binti Saiful Bahri (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
Muslim women are often portrayed and perceived in a negative light in the dominant Western narrative, especially in the post-9/11 era. Western misconceptions of Islam have proliferated a distorted identity of Muslims. For the Muslim diaspora, struggling with hyphenated identity has further complicated their image as Muslims, which is especially the case with Muslim women. This study examines the process of identity formation of contemporary diasporic Muslim women living in America. The two works chosen are Mohja Kahf's The Girl in the Tangerine Scarf (2006) and Umm Zakiyyah's Realities of Submission (2008). The discussion is based on each writer's representation of the Muslim self with various themes including challenging the Western stereotypes of Muslims, confronting the identity crisis as well as overcoming differences between culture and religion. The novels are analyzed as bildungsroman texts, as this study discusses the characters' spiritual journey and the development of Muslim identity. The study demonstrates how Islam gives Muslim women a sense of identity through the wearing of hijab and performing salah (prayer). Apart from examining the authors' ability to counter the perceptions of Muslims that are often negative, this study investigates how women are empowered in the selected novels by way of showing that their characters are able to exercise their volitions on issues raised within the texts while maintaining their identity as Muslims.